Charge transfer enhancement at the CZTS photocathode interface using ITO for efficient solar water reduction - Tay, Ying Fan (2024)
Cu2ZnSnS4 (CZTS) is considered as one of the most promising photocathodes for photoelectrochemical (PEC) water splitting due to its suitable optoelectronic properties. However, its PEC performance and stability degrade due to the poor interface between buffer layer CdS and catalyst Pt. In this work, indium tin oxide (ITO) was investigated as a charge transfer and protective layer for the CZTS/CdS/Pt photocathode. The solution-processed CZTS thin film coated with a CdS/ITO double layer and Pt catalyst (CZTS/CdS/ITO/Pt) yielded a photocurrent of 29 mA cm−2 at 0 VRHE and an onset potential of 0.75 VRHE, which is significantly higher than that of the pristine CZTS/CdS/Pt photocathode. More importantly, the addition of the ITO layer was found to have a “recovery” effect that enables the CZTS/CdS/ITO/Pt photocathode to remain stable under photo-reducing conditions, as confirmed by dark linear sweep voltammetry runs after a stability test. Our results suggest that the improved photocurrent, onset potential, and recovery effect are probably attributed to the removal of phosphate ions adhering to the surface of the ITO layer and higher catalytic activity at the semiconductor/electrolyte surface by forming In-Pt and Sn-Pt interactions due to partial reduction of In and Sn on the ITO surface.